Human pulp response after an adhesive system application in deep cavities - Hebling, J.; Giro, EMA; Costa, CAS (Elsevier B.V., 1999)
Objectives: To evaluate the pulpo-dentin complex response to a dentin adhesive application in deep cavities performed in human teeth.Methods: Deep class V cavities were prepared on the buccal surface of 46 premolars. The remaining dentin of the axial wall received 10% phosphoric acid and dentin adhesive (group DA), or was protected before the acid and dentin adhesive application with calcium hydroxide cement (group CH). Half of the teeth, which received the acid application directly over the axial wall, were contaminated prior to the procedures with dental plaque collected from the patient's own teeth (group DAC). The plaque was placed on the dentin for 5 min and then the cavity was washed. All teeth were restored with a light-cured composite resin. The teeth were extracted after 7, 30 or 60 days and prepared according to normal histologic techniques. Serial sections were stained with WE, Masson's trichrome and Brown & Brenn technique for demonstration of bacteria.Results: the histopathologic evaluation showed that in groups DA and DAC, the inflammatory response was more evident than in group CH. Also, the intensity of the pulp reaction increased as the remaining dentin thickness decreased. There was no statistical difference in the inflammatory response between the groups DA and DAC.Conclusion: Based on the experimental conditions, we concluded that the All Bond 2 adhesive system, when applied on dentin in deep cavities, showed an acceptable biocompatibility. However, the intensity of the pulpo-dentin complex response depends on the remaining dentin thickness. (C) 1999 Elsevier B.V. Ltd. All rights reserved.
Keywords: biocompatibility; adhesive resin; dentin; human tooth